OVERVIEW AND GENERAL CONCEPTS - Jonhson C.M.; Beard B.L.; Albarède F. (My University, 2004)
Of the eighty-three naturally occurring elements that are not radioactive or have half lives long enough to be considered stable (>109 yrs), nearly three-quarters have two or more isotopes. Variations in the isotopic ratios of a number of these elements, including H, C, N, O, and S, provide the foundation for the field of stable isotope geochemistry. Investigations of variations in the isotopic compositions of these traditional elements have provided important constraints on their sources in natural rocks, minerals, and fluids. These studies have focused on a range of problems including planetary geology, the origin and evolution of life, crust and mantle evolution, climate change, and the genesis of natural resources. Much less attention, however, has been paid to stable isotope variations of other elements that are also geochemically important such as certain metals and halogens. In part this has been due to analytical challenges, although first-order variations for several systems have been constrained using long-standing analytical methods such as gas- and solid-source mass spectrometry. With the advent of analytical instrumentation such as multi-collector, inductively-coupled plasma mass spectrometry (MC-ICP-MS), large portions of the Periodic Table are now accessible to stable isotope studies.